2015
DOI: 10.1111/jdi.12388
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atherosclerosis‐related risk factors on serum high‐sensitivity C‐reactive protein levels in patients with type 2 diabetes: Comparison of their influence in obese and non‐obese patients

Abstract: Aims/IntroductionIncreased levels of high‐sensitivity C‐reactive protein (hs‐CRP) likely leads to the development of atherosclerosis. Therefore, it is very important to know which factors largely influence hs‐CRP levels. In the present study, we examined the influence of various atherosclerosis‐related factors on hs‐CRP levels in patients with type 2 diabetes.Materials and MethodsA total of 275 patients (176 men, 99 women) were enrolled in this study. We tested the relationship between the number of risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
2
7
0
2
Order By: Relevance
“…Various biological mechanisms are postulated to be involved in inflammation‐diabetes relationship. In this study, the main mediator was found to be BMI, which is in line with the recent study of Shimoda et al, who demonstrated that BMI is an important predictor of CRP only among obese patients with diabetes . Obesity‐induced insulin resistance begins in adipose tissue.…”
Section: Discussionsupporting
confidence: 91%
“…Various biological mechanisms are postulated to be involved in inflammation‐diabetes relationship. In this study, the main mediator was found to be BMI, which is in line with the recent study of Shimoda et al, who demonstrated that BMI is an important predictor of CRP only among obese patients with diabetes . Obesity‐induced insulin resistance begins in adipose tissue.…”
Section: Discussionsupporting
confidence: 91%
“…One of the explanations was eGFR levels did not appear to influence the serum CRP levels, especially in those with early stage CKD (28). Serum CRP was independently associated with albumin, CVEs, and B2M (28)(29)(30). As previous study, the discriminative power of B2M for death was superior to CRP and renal function (30).…”
Section: Discussionmentioning
confidence: 68%
“…Hs-CRP is an acute-phase index of micro-inflammatory response that can activate the complement system in the body and enhance the leukocyte phagocytosis by binding to the chromatin and can play a regulatory role by stimulating cell activation ( 16 ). Hs-CRP can cause inflammatory response of the body, which is an important pathological process of DN ( 17 ).…”
Section: Discussionmentioning
confidence: 99%